2012
DOI: 10.1073/pnas.1217012109
|View full text |Cite
|
Sign up to set email alerts
|

Category-selective phase coding in the superior temporal sulcus

Abstract: Object perception and categorization can occur so rapidly that behavioral responses precede or co-occur with the firing rate changes in the object-selective neocortex. Phase coding could, in principle, support rapid representation of object categories, whereby the first spikes evoked by a stimulus would appear at different phases of an oscillation, depending on the object category. To determine whether object-selective regions of the neo-cortex demonstrate phase coding, we presented images of faces and objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 61 publications
(101 reference statements)
4
29
0
Order By: Relevance
“…By finding evidence for such a temporal multiplexing in the beta frequency band we critically extend previous reports of phase encoding of information for object features, object identities, and object categories at theta, alpha and gamma frequencies (Kayser et al, 2012;Siegel et al, 2009;Turesson et al, 2012;Womelsdorf et al, 2012). In our study, the beta rhythmic phaseof-firing multiplexing applied to complex learning variables that were needed to succeed in the behavioral learning task.…”
Section: Multiplexing Of Information Through Phase-of-firing Encodingsupporting
confidence: 85%
“…By finding evidence for such a temporal multiplexing in the beta frequency band we critically extend previous reports of phase encoding of information for object features, object identities, and object categories at theta, alpha and gamma frequencies (Kayser et al, 2012;Siegel et al, 2009;Turesson et al, 2012;Womelsdorf et al, 2012). In our study, the beta rhythmic phaseof-firing multiplexing applied to complex learning variables that were needed to succeed in the behavioral learning task.…”
Section: Multiplexing Of Information Through Phase-of-firing Encodingsupporting
confidence: 85%
“…Previous studies in both humans and nonhuman primates have identified category-specific phase coding of objects, where different object categories have different preferred phases associated with neural activity (Turesson et al, 2012;Watrous et al, 2015b). Here, we go beyond phase dissociations between different categories, by showing that the variability in phase information relates to variability in the stimulus properties, and is the case for both visual and semantic properties.…”
Section: Discussionmentioning
confidence: 65%
“…Oscillations are a ubiquitous property of the brain, and are known to be modulated by various aspects of vision and memory in humans (Fell and Axmacher, 2011;Hanslmayr et al, 2012;Helfrich and Knight, 2016;Jensen et al, 2014;Watrous et al, 2015a). Recent studies have begun to show how the ongoing phase of an oscillation can be used to decode specific stimuli (Lopour et al, 2013;Ng et al, 2013;Schyns et al, 2011;Turesson et al, 2012;Watrous et al, 2015b). These studies have shown that frequency-specific activity can be used to decode the specific features of visual objects, or object categories, suggesting that oscillatory phase could provide a mechanism for encoding stimulus information within a region.…”
Section: Introductionmentioning
confidence: 99%
“…The gamma‐band phase with the strongest unit activity could vary across condition (Senior et al, ; Colgin et al, ; Turesson et al, ; Womelsdorf et al, ) independent of the strength of locking. Thus, in addition to the spike‐field coherence, we extracted the instantaneous phase from the 50–70 Hz band using the Hilbert transform to see if the peak MUA responses occurred at different phases of gamma as a function of scene repetition.…”
Section: Resultsmentioning
confidence: 99%